The Problems of State Regulation of the Internal Forced Migration in Ukraine - Shvets, Iryna; Sled, Oleksandra; Liashok, Yaroslav; Hryhoryeva, Olesya (International Journal of Engineering and Technology, 2018)
The aim of this study is to determine the main areas of the state regulation of the internal forced migration in Ukraine. It is underlined that prevention of displacement and protection of IDPs and other affected population within its own country are the responsibility of state authorities. The number of internally displaced persons in Ukraine in 2014–2018 is analysed. The study of trends in the number of IDPs was carried out on the example of Pokrovsk town. Key feature of the forced migration processes in both Pokrovsk and Ukraine is explored and defined. It is the tendency to stabilization of the percentage of various migrants’ categories during the whole period of armed conflict. Characteristics of the statistical assessment of internally displaced persons in Ukraine are generalized. Its drawbacks and consequences are formulated. Impact of the forced migration on the internal situation in the country is identified. Based on SWOT-analysis, possibilities, significant threats, strengths and weaknesses for determining the comparative advantages and obstacles of the state regulations for internal forced migration processes are established. The objects and priority areas for the state regulation of internal forced migration processes are described. The economic and social-psychological adaptation as the main directions of the state regulation of internal forced migration is reviewed.